2008
DOI: 10.1515/comm.2008.024
|View full text |Cite
|
Sign up to set email alerts
|

Partners' influence on each other's television exposure: Dominance or symmetry?

Abstract: In this study we analyzed to what extent partners who share the same household affect each other's exposure to television. With the use of linear structural equation modeling we analyzed data from a large scale representative survey in The Netherlands (n 697 couples).Results indicate that both men and women influence their partner's exposure to television.When people spend much time watching television, their partners are also likely to spend a lot of time in front of the television. These influences on each o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Kraaykamp et al (2007) have studied how the individual frequency of media use in Dutch couples is the result of both spouses' statuses. Similarly, Konig et al (2008) have looked at Dutch partners' reciprocal influence on average time spent watching TV. Finally, through a more qualitative-analysis approach, Silva and Le Roux (2011) have stressed different cultural capital and gender patterns in the cultural participation of British couples.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kraaykamp et al (2007) have studied how the individual frequency of media use in Dutch couples is the result of both spouses' statuses. Similarly, Konig et al (2008) have looked at Dutch partners' reciprocal influence on average time spent watching TV. Finally, through a more qualitative-analysis approach, Silva and Le Roux (2011) have stressed different cultural capital and gender patterns in the cultural participation of British couples.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although we have found a few studies supporting the argument that partners influence each other's media choices (Konig et al, 2008;Kraaykamp et al, 2007), we have found no studies that directly test the argument concerning the mediating role of household preferences in the correlation between partners' media choices. To fill this gap in knowledge, we have developed a number of hypotheses concerning the development of household television preferences and concerning the influence exerted by household television preferences on the viewing choices of household members.…”
Section: Partners and Genre Choicesmentioning
confidence: 71%
“…A process of mutual influence may also be present in partners' choices for television genres; indeed, a few studies have provided support for the argument that partners influence each other's media choices. For instance, Konig et al (2008) and Kraaykamp et al (2007) both find negative effects of partner's educational level on the primary respondent's television consumption-with higher educational levels resulting in less TV consumption. Furthermore, Kraaykamp et al (2007) find positive effects of partner's educational level on primary respondent's literary book reading-with higher education resulting in more reading.…”
Section: Partners and Genre Choicesmentioning
confidence: 99%
“…To be fair, treating parents as a single unit may be an acceptable practice because romantic partners exert influence on each other's media habits (e.g., Konig et al, 2008;Vettehen et al, 2012). However, previous studies on the development of reading habits have shown that fathers and mothers individually influenced their offspring's reading habits (e.g., Mullan, 2010;Wollscheid, 2013Wollscheid, , 2014.…”
Section: Distinguishing Maternal From Paternal Influencementioning
confidence: 99%
“…People who prefer news are more likely to engage in politics than those who do not (Bakker & de Vreese, 2011;Quintelier & Hooghe, 2011;Rittenberg, Tewksubry, & Casey, 2012). More importantly, news preference developed at the adolescent stage tends to persist over time (e.g., Konig, Kraaykamp, & Westerik, 2008;Notten & Kraaykamp, 2009;York & Scholl, 2015) and potentially widen the knowledge gap between the politically engaged and disengaged (e.g., Moeller & de Vreese, 2015). Hence, the development of preference for TPAC is a key part of the political socialization process, which could promote political learning and participation during and after adolescence.…”
mentioning
confidence: 99%